Metabolic and proteomic signatures of hypoglycaemia in type 2 diabetes. Issue 4 (27th December 2018) - Halama, Anna; Kahal, Hassan; Bhagwat, Aditya M.; Zierer, Jonas; Sathyapalan, Thozhukat; Graumann, Johannes; Suhre, Karsten; Atkin, Stephen L.
Abstract : Aims: To determine the biochemical changes that underlie hypoglycaemia in a healthy control group and in people with type 2 diabetes (T2D). Materials and methods: We report a hypoglycaemic clamp study in seven healthy controls and 10 people with T2D. Blood was withdrawn at four time points: at baseline after an overnight fast; after clamping to euglycaemia at 5 mmol/L; after clamping to hypoglycaemia at 2.8 mmol/L; and 24 hours later, after overnight fast. Deep molecular phenotyping using non‐targeted metabolomics and the SomaLogic aptamer‐based proteomics platform was performed on collected samples. Results: A total of 955 metabolites and 1125 proteins were identified, with significant alterations in >90 molecules. A number of metabolites significantly increased during hypoglycaemia, but only cortisol, adenosine‐3′, 5′‐cyclic monophosphate (cyclic AMP), and pregnenolone sulphate, were independent of insulin. By contrast, identified protein changes were triggered by hypoglycaemia rather than insulin. The T2D group had significantly higher levels of fatty acids including 10‐nonadecenoate, linolenate and dihomo‐linoleate during hypoglycaemia compared with the control group. Molecules contributing to cardiovascular complications such as fatty‐acid‐binding protein‐3 and pregnenolone sulphate were altered in the participants with T2D during hypoglycaemia. Almost all molecules returned to baseline at 24 hours. Conclusions: The present study provides a comprehensive description of molecular events that are triggered by insulin‐induced hypoglycaemia. We identified deregulated pathways in T2D that may play a role in the pathophysiology of hypoglycaemia‐induced cardiovascular complications.